Inclusive Businesses in Peru: Including the BoP in the Supply Chain of Corporations - Faura, Cynthia Faura Beraún (2011)
The question of how to make Corporate Social Responsibility (CSR) sustainable within a corporation has haunted both CSR practitioners and academics. The answer has often been that it should be placed in the core of the corporations’ strategy, allowing a win-win situation for corporations and society. However, this has been hard to translate to everyday practice. On the other hand, the debate around whether corporations should take part in the fight against poverty seems to never end.